Serum visfatin levels in patients with axial spondyloarthritis and their relationship to disease activity and spinal radiographic damage: a cross-sectional study - Hulejová, Hana; Kropáčková, Tereza; Bubová, Kristýna; Kryštůfková, Olga; Filková, Mária; Mann, Heřman; Forejtová, Šárka; Tomčík, Michal; Vencovský, Jiří; Pavelka, Karel; Šenolt, Ladislav (Rheumatology international, 2019)
The purpose of this cross-sectional study was to assess the visfatin levels in patients with axial spondyloarthritis (axSpA) and to investigate the association between visfatin, disease activity and radiographic spinal damage. Serum visfatin levels were determined by enzyme-linked immunosorbent assay in 64 patients with axSpA (46 with radiographic axSpA (r-axSpA) and 18 with non-radiographic axSpA (nr-axSpA)) and 61 age-/sex-matched healthy individuals. Patients with r-axSpA were further divided into two subsets based on radiographic spinal damage using modified Stoke Ankylosing Spondylitis Spine Score (mSASSS = 0 and mSASSS ≥ 1). The Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) was used to assess disease activity. C-reactive protein (CRP) levels and human leukocyte antigen (HLA)-B27 were determined. Visfatin levels were significantly higher in patients with axSpA and in the subgroup of patients with r-axSpA than in healthy individuals (p = 0.010 and p = 0.005, respectively), with no difference between patients with r-axSpA and with nr-axSpA. In general, disease activity was high (mean BASDAI 5.01) and was moderately correlated with visfatin levels (r = 0.585; p = 0.011) in patients with nr-axSpA. Visfatin levels correlated with mSASSS (r = 0.281; p = 0.026) and were significantly higher in axSpA patients with mSASSS ≥ 1 than in those with mSASSS = 0 (p = 0.025). Our study showed that circulating visfatin levels are elevated in axSpA patients, may be associated with disease activity in early phase of the disease and with the degree of radiographic spinal involvement.
Keywords: dospělí; Magnetic Resonance Imaging; Female; Cytokines; Adult; ženské pohlaví; průřezové studie; Sacroiliac Joint; cytokiny; lidé; nikotinamidfosforibosyltransferasa; bederní obratle; magnetická rezonanční tomografie; Nicotinamide Phosphoribosyltransferase; studie případů a kontrol; krční obratle; sakroiliakální kloub; páteř; Spine; Cross-Sectional Studies; Male; Case-Control Studies; Lumbar Vertebrae; Spondylarthropathies; lidé středního věku; Cervical Vertebrae; mužské pohlaví; spondylartropatie; Middle Aged; Humans